Tax evasion and enforcement: How efficient tax authorities can be the key to combating tax avoidance (Research, Society and Development, 2023)
This article aims to present the active supervision by the State as an effective way to combat tax evasion and the consequences that derive from it. To achieve this goal, the current research employed the methodology of narrative literature review. In summary, the article is divided into four, namely: the first consisting of the introduction of the work; the second that deals with the methodology; the third part deals with the results and discussions and encompasses the following points: the Power to Tax of the State, the legal aspects of Tax Evasion and the importance of State oversight as a way to combat Tax Evasion; finally, the last part that concerns the final considerations of the research, which demonstrate that an effective oversight by the State is the most effective way in the fight against tax evasion and its consequences in society.